Fatty acid profi le in erythrocytes associated with serum cytokines in pediatric cystic fi brosis patients - Pereira da CUNHA, Ana Lucia; Carioca da COSTA, Ana Carolina; VASCONCELOS, Zilton; TAVARES DO CARMO, Maria das Graças; Moutinho de Miranda CHAVES, Celia Regina (Revista de Nutrição, 2023)
Objective To analyze erythrocyte fatty acid composition and its association with serum cytokine levels in pediatric cystic fi brosis patients. Methods A cross-sectional study was performed at a reference center in Rio de Janeiro, Brazil. We have included all pediatric patients aged 5-19 years with confirmed cystic fibrosis diagnosis. Erythrocyte fatty acid composition and serum cytokine (TNF-α, IL-1β, IL-6 and IL-8) and C-reactive protein levels were measured. The cut-off point to determine essential fatty acids deficiency was the linoleic acid concentration of <21%. Results Twenty-six children (<10 years old) and thirty-one adolescents were studied. Most patients were female and heterozygous for DF508 mutation and suffered from exocrine pancreatic insufficiency. Both children and adolescents had lower linoleic acid concentration (<21%). TNF-α was the only pro-inflammatory marker whose levels were increased; the increase was greater in children. An association between fatty acid composition in erythrocytes and cytokines IL-1β and IL-6 was observed (p<0.05). Conclusion The pediatric cystic fibrosis patients studied presented a deficiency of essential fatty acids, and an association between fatty acid profile in erythrocytes and serum pro-inflammatory cytokines was observed. These findings highlight the importance of this type of assessment that may open new possibilities for studying pathophysiology and treating cystic fibrosis patients, such as the dietary supplementation with n-3 fatty acids (eicosapentaenoic and docosahexaenoic acids). However, further longitudinal studies are needed for better clarification of the imbalance in lipid metabolism and inflammation in cystic fibrosis.